Valuation on the use of the advantages of the pacific alliance by SMEs in Northwestern Mexico - Becerra-Perez, Luis Armando; Sánchez-Meléndez, Eduardo Pabel (Unidad Editorial UPTC, 2020)
There are advantages for companies and citizens in trade agreements signed between countries. Depending on the degree of internationalization of companies and the efforts of government promotion, these advantages can be more or less exploited. In this way, this article analyzes the process of internationalization of a company, which in the framework of the Pacific Alliance (PA) trade agreement began exports to the signatory countries of the deal and presents the results of a survey applied in northwestern Mexico. The evidence found shows that the process of internationalization of the company (SMEs) is gradual, growing up requires resources, support, knowledge, and consists of stages, for which the company needs to identify its competitive advantages and its ability to internalize them. Besides, it validates the existence of low usage of the benefits contemplated by the PA by the exporting companies in the region, given their limited knowledge of the agreement and the lack of government promotion. Keywords: Pacific Alliance, Free Trade Agreement, Internationalization of SMEs JEL Codes: F13, F14, F15 Received: 04/06/2019. Accepted: 12/02/2020.  Publicado: 27/04/2020